BONSOIR IDER MOI SI VOUS PLAIT !!!!!

factoriser les expressions suivantes:

A=6x²+7x

B=8x-9x²

E=(4x-2)²+(4x-2)(5x-4)


F=(5x-3)(2x+6)+4(2x+6)


G=(6x-5)(6x+4)+(6x-5)


H=(3x-5)²+3x-5

J=(3x+2)²+(3x+2)(5x-4)


K=(4x+5)²-(4x+5)

N=(3x+5)²-(3x+5)(7x+4)


P=(6x-8)²-6x+8

1

Réponses

2014-02-10T20:40:14+01:00
A=6x²+7x
A=x(6x+7)
B=8x-9x²
B =x(8-9x)
E=(4x-2)²+(4x-2)(5x-4)  
E = (4x-2)(4x-2 +5x-4)
E = (4x-2)(9x-6))
F=(5x-3)(2x+6)+4(2x+6) 
F = (2x+6)(5x-3+4)
F = (2x+6)(5x+1)
G=(6x-5)(6x+4)+(6x-5) 
G =(6x-5)(6x+4+1)
G = (6x-5)(6x+5)
H=(3x-5)²+3x-5
H = (3x-5)(3x-5+1)
H = (3x-5)(3x-4)
J=(3x+2)²+(3x+2)(5x-4) 
J = (3x+2)( 3x+2+5x-4)
J = (3x+2)( 8x-2)
K=(4x+5)²-(4x+5)
K = (4x+5)(4x+5-1)
K = (4x+5)(4x+4)
N=(3x+5)²-(3x+5)(7x+4) 
N = (3x+5)(3x+5-7x-4)
N = (3x+5)(-4x+1)
P=(6x-8)²-6x+8
P=(6x-8)²-(6x-8)
P = (6x-8)(6x-8-1)
P = (6x-8)(6x-9)